Evaluation of Different Chemical Insecticides and Biopesticides Against Vegetable Leaf Miner, Liriomyza Sativae in Tomato: Insecticides and Bio-Pesticides for Control of Leaf Miner in Tomato - Das, Krishna Rani (SAARC Journal of Agriculture, 2025)
Vegetable leaf miner once considered as a secondary pest is now emerging as a primary pest of vegetables including tomato. It is also considered as an A1quarantine pest. Two experiments were performed to evaluate the efficacy of various insecticides against vegetable leaf miner in entomology laboratory and central farm of Sher- e- Bangla Agricultural University during October, 2019 to April, 2020. Seven insecticides such as Imidachloprid, Lamda cyhalothrin, Emamectin benjoate, Spinosad, abamectin, Matrine, azadirachtin at recommended dosages were evaluated to control vegetable leaf miner at both laboratory and field condition. In case of laboratory experiment, treatments were evaluated using leaf dip technique in a completely randomized design (CRD) with three replications. In field study the treatments were laid in a completely randomized block design with three replications using Tomato as a host plant. Among all the tested chemical and bio pesticides, Proclaim 5SG ) @ 1.0g L-1 water, Tracer 45SC @ 0.4 ml L-1water and Vertimec 018 EC@ 1.2 ml L-1water were most effective against Liriomyza leaf miner in both condition. Thus three timely sprays of any one of these pesticides viz. Proclaim 5SG, Tracer 45SC and Vertimec 018 EC at recommended dosages could be helpful to reduce the infestation of vegetable leaf miner. SAARC J. Agric., 22(2): 227-238 (2024)